Beyond the fridge: Opening zones of agency with young artists - Bauberger, Nicole (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
Covid introduced constraints into art and art education programming which challenged art programmers and educators to consider the art of the possible. I will draw on my art and teaching practices during that time as well as my stint as emerging curator of the Yukon Arts Centre Youth Gallery to consider how working locally and outdoors, with a view to future use of the artworks made, shaped successful programs. I will share images and reflections from the Winter Garden, the Monster Parade, and interactive works in the Dalton Trail Trail Gallery, considering the following questions: How does making artwork that has a plan for use in public presentation change the art learning environment? What new levels of unanticipated meaning occur when student artwork encounters its wider community? What opportunities did Covid-related constraints open for us, and what should we make sure and carry with us into the future?